Mediterranean diet and non-alcoholic fatty liver disease: new therapeutic option around the corner? - Sofi, Francesco; Casini, Alessandro (World journal of gastroenterology : WJG, 2014)
Non-alcoholic fatty liver disease (NAFLD) represents the most common chronic liver disease in Western countries, being considered as the hepatic manifestation of metabolic syndrome. NAFLD has a common pathogenic background to that of metabolic syndrome, and shares many risk factors such as obesity, hypertension, insulin resistance and dyslipidemia. Although there is no currently available evidence-based established treatment for NAFLD, all the recommendations from the medical associations indicate that the most effective treatment is to reduce weight through lifestyle modifications. Diet, indeed, plays a key role in the management of NAFLD patients, as both the quantity and quality of the diet have been reported to have a beneficial role in the onset and severity of the liver disease. Among all the diets that have been proposed, a Mediterranean diet was the most effective dietary option for inducing weight loss together with beneficial effects on all the risk factors associated with metabolic syndrome and NAFLD. Over the last few years, research has demonstrated a beneficial effect of a Mediterranean diet in NAFLD. In this review, we will examine all the available data on the association between diet, nutrients and the Mediterranean diet in association with onset and severity of NAFLD.